Produktifitas Alat Dan Pekerja Pada Pengecoran Plat Dan Balok Lantai Gedung (Studi Kasus Pembangunan Proyek Gedung FMIPA Universitas Brawijaya) - Yenny Yenny; M. Ruslin Anwar; Yulvi Zaika (Rekayasa Sipil, 2014)
This study discusses the tools and labor productivity, on the work of casting plate/beam on the 4 floor (Zone 2), and the 5 th floors. That’s on the 4 th floor of the tools used concrete pump, while on the 5 floor using a tower crane. Therefore it can be identified that the tool and the labor affect the casting productivity of resulting. By the casting productivity, it can be seen how much influence the factors of tools and labor on the productivity, so as to know which factors are the most substantial influence on the increase in productivity. There are two kinds of data are qualitative (by questionnaires) and quantitative (field observation). Where tools (X 1 ) and labors (X 2 ) as independent variables, productivity (Y 1 JURNAL REKAYASA SIPIL / Volume 8, No.2 – 2014 ISSN 1978 - 5658 th ) and the quality of concrete (Y ) as the dependent variables. All data were tested first by test validity, reliability, and coefficient of determination, prior to the hypothesis testing. By the data analysis, we concluded that the variable of tool affect the productivity on the task of casting plate/beam on 4 th floor, while on the 5th floor affected by the variable of labor. On 4 th floor the value of the casting productivity is greater than on the 5 th floor. Thus, it can be indicated that the increase in the height of the floor, so then productivity will decrease.